Vasoactive intestinal polypeptide level in gastroesophageal reflux disease before and after surgical treatment - Haidarzhi, Ye. I.; Holovko, M. H.; Okhrimenko, H. O. (Zaporozhye Medical Journal, 2023)
From year to year, wide spread of gastroesophageal reflux disease (GERD) is attracting greater attention of specialists in the field of this pathology diagnosis and treatment. In-depth studies on etiological and pathogenetic factors in the GERD development are being conducted. Of particular interest is the role of humoral factors, one of which is vasoactive intestinal peptide (VIP). There are currently no data on the dynamics of this hormone during surgical treatment of GERD. The aim of the study was to examine the dynamics of plasma VIP during surgical treatment of GERD and its influence on the lower esophageal sphincter (LES) function. Materials and methods. Surgical treatment in the Nissen modification was performed for 35 patients with GERD. There were 26 women (74.3 %), men – 9 (25.7 %). mean age – 55.3 ± 11.3 years. Comparison group – 20 apparently healthy individuals: women – 14 (70.0 %); men – 6 (30.0 %), mean age – 56.7 ± 10.6 years. VIP was measured in venous blood plasma by an enzyme immunoassay (Vasoactive intestinal peptide ELISA, S-1201, BCM Diagnostics) using an immunoenzyme complex ImmunoChem-2100 (USA). The sampling of the studied samples in the main group was carried out before the operation and 2–3 months post-surgery. Results. In the main group before the surgery, the level of VIP was 3.1 ± 1.1 ng/ml, after the surgery – 2.2 ± 1.0 ng/ml. In the comparison group, VIP was determined at the level of 2.1 ± 1.1 ng/ml. In GERD before the surgery, the VIP level was statistically different from the indicators in the comparison group and from postoperative values. After surgical treatment, VIP values were decreased to the level of apparently healthy individuals. There was a positive correlation between the VIP level and acid exposure time (AET), the total number of refluxes, the number of reflux events longer than 5 minutes, the maximum duration of refluxes and the degree of esophageal inflammation. Conclusions. In the surgical treatment of GERD, the statistically significant decrease in the VIP level to that of apparently healthy individuals is determined. The moderate positive correlation between the levels of VIP, AET, the average number of refluxes, the number of reflux events longer than 5 minutes, and the maximum duration of refluxes confirms the inhibitory effect of VIP on LES tone. The relationship between the degree of esophageal inflammation and the VIP level confirms the indirect, through the action of VIP, inhibitory effect of the esophagitis severity on the LES tone.